Lyman-alpha spectroscopy of extreme [O iii] emitting galaxies at z ≃ 2-3: implications for Lyα visibility and LyC leakage at z > 6. Issue 3 (10th March 2021) - Tang, Mengtao; Stark, Daniel P; Chevallard, Jacopo; Charlot, Stéphane; Endsley, Ryan; Congiu, Enrico
ABSTRACT: Spectroscopic observations of massive z > 7 galaxies selected to have extremely large [O iii ] + H β equivalent width (EW ∼1500 Å) have recently revealed large Ly α detection rates, in contrast to the weak emission seen in the general population. Why these systems are uniquely visible in Ly α at redshifts where the intergalactic medium (IGM) is likely significantly neutral is not clear. With the goal of better understanding these results, we have begun a campaign with MMT and Magellan to measure Ly α in galaxies with similar [O iii ] + H β EWs at z ≃ 2–3. At these redshifts, the IGM is highly ionized, allowing us to clearly disentangle how the Ly α properties depend on the [O iii ] + H β EW. Here, we present Ly α EWs of 49 galaxies at z  = 2.2–3.7 with intense [O iii ] + H β line emission (EW = 300–3000 Å). Our results demonstrate that strong Ly α emission (EW >20 Å) becomes more common in galaxies with larger [O iii ] + H β EW, reflecting a combination of increasingly efficient ionizing photon production and enhanced transmission of Ly α. Among the galaxies with the most extreme [O iii ] + H β emission (EW ∼1500 Å), we find that strong Ly α emission is not ubiquitous, with only 50 per cent of our population showing Ly α EW >20 Å. Our data suggest that the range of Ly α strengths is related to the observed ellipticity, with those systems that appear edge-on or elongated having weaker Ly α emission. We use these results to interpret the anomalous Ly α properties seen in z > 7 galaxies with extreme [O iii ] + H β emission and discuss implications for the escape of ionizing radiation from these extreme line emitting galaxies.